ANALYSIS OF ANTIOXIDANT ACTIVITY OF LIDAH MERTUA LEAVES (Sansevieria trifasciatalauretii) USING DPPH METHOD - Dwi Cahya Putra I M; Bogoriani N W (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
Lidah mertua plant has the potential as a natural antioxidant and the antioxidant activity of a plant depends on the number of active compounds extracted. This study aims to determine the yield, total phenol content, total flavonoid content, and IC50 value of lidahmertua leaf extract macerated with ethanol, ethyl acetate, and n-hexane as solvents, and to determine the compounds contained in the lidahmertua leaf extract which have activity antioxidants. The results of the phytochemical test of the lidahmertua leaf extract showed positive results containing polyphenolic compounds, flavonoids, saponins, alkaloids, and steroids. The maceration yield of each solvent was 12.13%, 10.15% and 8.11%, respectively. While the measurement results of the total phenol content of each solvent were 6.96; 3.67; and 1.94 mg GAE/g. The results of the measurement of the flavonoid content of each solvent were 5.82; 3.28; and 1.71 mg QE/g. The IC50 values for each solvent were 162.135 mg/L, 184.561 mg/L and 206.265 mg/L. The extract which has the highest total phenol content, total flavonoid content, and antioxidant activity is in ethanol solvent.